Variation in morphological characters of Marsilea crenata living in floating aquatic, emergent aquatic, and terrestrial habitats - WISANTI WISANTI; DURAN COREBIMA ALOYSIUS; Siti Zubaidah; SRI RAHAYU LESTARI (Society for Indonesian Biodiversity, 2021)
Abstract. Wisanti, Aloysius DC, Zubaidah S, Lestari SR. 2021. Variation in morphological characters of Marsilea crenata living in floating aquatic, emergent aquatic, and terrestrial habitats. Biodiversitas 22: 2853-2859. Marsilea is a hydrophyte fern that has plasticity often influenced by enviroment. Several of the species with different habitats or geographies show morphological variations. Therefore, this study aims to analyze the variations in morphological characters of M. crenata growing in aquatic and terrestrial habitats. A total of 38 plant samples were collected from their natural habitats including floating aquatic, emergent aquatic, and terrestrial types. Morphological variations data included 4 qualitative characters and 9 quantitative characters. The quantitative characters were analyzed by one-way ANOVA to test for differences, while the combination of both characters was analyzed using Principal Component Analysis (PCA) to determine the distribution between groups. The data results showed a separate grouping pattern between aquatic and terrestrial populations. These two groups showed significant differences in 5 quantitative characters and 2 qualitative characters. However, emergent aquatic samples’ distribution pattern is closer to the terrestrial group. The characters’ similarity of these two populations was in ??the rhizomes air spaces area, the position between leaflets and absence of red streak on the abaxial lamina. Conclusively, the variations in M. crenata’s morphological characters indicate that this plant has experienced morphological adaptations to water availability in its environment.